Methodology for Analysing Capacity and Level of Service for Roundabouts with one Lane (HCM 2000) - Ivana Nedevska, Slobodan Ognjenovic, Vera Murgul (Procedia Engineering 187, pp 797-802, 2017)
As the motorisation augments in urban areas, different solutions are required, considering the traffic network. In order to adjust the urban arrangement with the need for mobility, complex process of planning and designing is required. City development contains adequate incertitude which causes difficulty during the process of planning and designing. According to this, the process of planning and designing the city infrastructure network are mutually connected and inevitable. Traffic planning is a base of successful functioning in urban areas. With adequate analysis about city development and traffic, the planning process can begin, and be followed by the designing process and building the traffic network. Analysis of capacity and level of service are necessary, in order to obtain the delay of the analysed facilities. These analyses can be empirical and analytical. The empirical model is based on regression analysis, and the analytical model uses the gap – acceptance theory. Empirical models provide better results, but can be used in cases where few roundabouts are congested, to calibrate the model. Othewise, gap – acceptance methods are used to analyse uncongested roundabouts.
Keywords: roundabout, capacity, level of service, Highway Capacity Manual, delay, gap – acceptance, planning, designing